The epidemiology and economic burden of hip fractures in Israel - Royi Barnea; Yossi Weiss; Ifat Abadi-Korek; Joshua Shemer (Israel Journal of Health Policy Research, 2018)
Abstract Background Hip fractures increase the risks of mortality and major morbidity in the elderly. Hip fractures are associated with chronic pain, reduced mobility, disability and increasing dependence. We evaluated the direct costs incurred to the Israeli healthcare system in 2013 as a result of hip fracture injuries in elderly patients. Methods Hip fractures costs evaluation consisted of first-year and long-term direct costs. Data on the incidence of hip fractures resulting in hospitalizations were retrieved from the Israeli Ministry of Health’s (MOH) Central Database of Hospital Admissions. Hospitalization, rehabilitation and nursing utilization rates and costs were estimated based on the professional literature and according to the MOH’s price list. Results During 2013, 6285 elderly patients were hospitalized in Israel due to hip fractures. Direct costs of hip fracture, comprising hospitalization, rehabilitation and nursing costs incurred during the first year after the injury, were estimated at 454 million New Israeli Shekels (NIS; 83,841 NIS per person). Long-term nursing care costs in 2013 were 265 million NIS, with an average cost of approximately 49,000 NIS for 1600 elderly persons receiving long-term nursing care as a result of a hip fracture. Overall, the total direct costs of hip fracture in the elderly population in Israel in 2013 were 719 million NIS. Conclusions The direct costs of hip fractures in Israel among the elderly are approximately 719 million NIS per year. The majority of costs are associated with the first year following the injury. To reduce healthcare costs in Israel, changes in the country’s healthcare policy on hip fractures are required. For example, there is a need for a program for detecting high- risk populations, and for early intervention following the injury.